Sejarah pabrik gula Buduran sebagai objek pembelajaran kolonial di Museum Mpu Tantular - Alfin Ganendra Albar; Eldin Warsito Suhantyo (Historiography: Journal of Indonesian History and Education, 2022)
This study tries to describe the history of the development of the Buduran sugar factory from 1835 to 1930 which will be useful for the Mpu Tantular Museum. This writing uses historical research methods which consist of several stages, namely topic selection, heuristics, criticism, interpretation, and historiography. Sidoarjo during the Dutch colonial period became a sugar industry area, this was because the area was suitable for planting sugar cane, so the colonial government exploited it by building a sugar factory there. One of the sugar factories in Sidoarjo that was established during the colonial period was the Buduran sugar factory, at this time the Buduran sugar factory has changed its function into a warehouse for engineers. Looking at the past, the Buduran sugar factory in its time continued to develop well and became a sugar contributor in Karesidan Surabaya. This Buduran sugar factory became one of the most successful factories of its time, with its production and area of sugar cane continuously growing. It is important to write the history of the Buduran sugar factory because it is only very small and can also contribute to the archives of the Mpu Tantular Museum as a place for learning from all walks of life. Penelitian ini mencoba menguraikan sejarah perkembangan pabrik gula Buduran pada tahun 1835 hingga 1930 yang akan bermanfaat bagi Museum Mpu Tantular. Penulisan ini menggunakan metode penelitian sejarah yang terdiri atas beberapa tahap yaitu pemilihan topik, heuristik, kritik, interpretasi dan historiografi. Sidoarjo pada masa kolonial Belanda menjadi wilayah areal industri gula, hal tersebut disebabkan karena wilayahnya yang cocok untuk ditanami tebu, maka pemerintah kolonial mengeksploitasi dengan membangun pabrik gula disana. Salah satu pabrik gula di Sidoarjo yang pernah berdiri pada masa kolonial adalah pabrik gula Buduran, pada masa kini pabrik gula Buduran sudah beralih fungsi menjadi tempat gudang penyimpanan zeni. Melihat masa lalu, bahwa pabrik gula Buduran ini pada masanya terus berkembang dengan baik dan menjadi penyumbang gula di Karesidenan Surabaya. Pabrik gula Buduran ini menjadi salah satu pabrik yang sukses pada masanya, dengan terus berkembang hasil produksi dan luas lahan tebunya. Pentingnya menulis sejarah dari pabrik gula Buduran, karena hanya sedikit sekali dan juga dapat memberi sumbangsi arsip terhadap Museum Mpu Tantular sebagai tempat pembelajaran dari semua kalangan.